Epidemiological Profile of Syphilis in Pregnant Women in the city of Macaé Rio de Janeiro - Liborio Neto, Adail Orrith; Santos, Juliane de Freitas; Goulart, Carlos Alexandre Ribeiro (Clinical and Biomedical Research, 2021)
Introduction:The gestational and congenital syphilis are diseases that can be prevented. Practices routinely carried out in prenatal care are effective for the prevention of cases. The prevalence of syphilis in pregnant women is considered an indicator of the quality of prenatal care. Objective:Define the epidemiological profile of pregnant women, in the city of Macaé – Rio de Janeiro, diagnosed with syphilis in the 2010-2018 period. Methodology: A cross-sectional study, retrospective, of the years 2010 to 2018 with assessment of general prevalence in the period and annual incidence rates in records and database of the Care Center of Women and Children and the Public Hospital of Macaé. Results:It was reported 535 cases of syphilis in pregnant women. 2018 had the highest number of reported cases (n = 151) with a detection rate of 38.4% per 1000 live births signifying an increase of 37% compared to 2010. Most cases were in the third trimester of pregnancy (n = 194 cases), in the age group 20-29 years (n = 322). Housewives (n = 248) were the most affected. Brown skin were 32.4% (n = 180) of the cases, followed by 16.9% (n = 124) black skin color. The majority (n = 124) had incomplete elementary school education. Among 2010 to 2018, the annual incidence rate of congenital syphilis increased from 1.4 to 17.2 cases per 1,000 live births. Conclusion:There was an increased prevalence of the disease in the city of Macaé, intensifying from 2015 with a peak of cases in 2018.